RekBen Tube with AR 3D for Electrical Flow among Vocational College Students - Nur Hazlina Abu Hassan; Che Zalina Zulkifli; Hasnatul Nazuha Hassan; Abu Bakar Ibrahim (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: The electric and electronic subject is one of the important subjects in vocational colleges. Admittedly, it is difficult to teach the concept of electrical flow based on the conventional method that relies on explanation using printed materials. The lack of technology-based materials has made it difficult for students to effectively learn such a concept. Against this background, this study was carried out to design, develop, and test a learning application based on Augmented Reality (AR) called RekBen Tube to help technical and vocational school students in learning the concept of electrical flow. Design: The methods used throughout the production of RekBen Tube application technology education learning tools are the ADDIE Model and the TAM Model. Findings: The actual image depiction of the electric current through the circuit is shown to clearly explain the movement of the electric current. Research limitations: This study has developed an application of 10 flip cards for scanning by RekBen Tube app to generate 3D images on each of the different picture cards. Practical implications: Much of the software used to produce this learning tool has been able to attract students to learn the basics of electricity. Paper type: Research Paper.